Socionutrition: The science of socionutrients - Sanjay Kalra,; Bharti Kalra,; Madhur Verma,; Nitin Kapoor, (Journal of the Pakistan Medical Association, 2025)
Nutrients are substances used by an organism to survive,grow and reproduce. ‘Social’ used in relation tocompanionship and society. In this opinion piece, wepropose and propound a novel concept, Socionutrition,and discuss the science of socionutrients, socionutrienttriggers and modifiers, as well as socionutrient abuse. Wediscuss these parameters in relation to health and exploretheir relevance to disease prevention and management. Keywords: Chronic disease, culinary medicine, diet,nutrition, social aspects